Projection of near-future anthropogenic PM2.5 over India using statistical approach. (August 2018) - Upadhyay, Abhishek; Dey, Sagnik; Goyal, Pramila; Dash, S.K.
Abstract: Particulate matter smaller than 2.5 μm (referred to as PM2.5 ) is the most important criteria pollutant impacting human health, environment and climate. India is already recognized as pollution hotspot where PM2.5 has been increasing in the recent past. Here we project anthropogenic PM2.5 for the near future (till 2040) over India using multiple linear regression (MLR) approach based on RegCM projected meteorology and ECLIPSE projected emission. MISR derived PM2.5 concentration (μg/m³) for the year 2010–2012 has been used to train the MLR model with reasonable accuracy (R > 0.9). The impact of the meteorological parameters under both RCP4.5 and 8.5 scenarios partially negates the impact of rising emission in future; more so in RCP8.5 than in RCP4.5 scenario. Air quality is projected to improve significantly with short lived climate pollutant (SLCP) 'mitigation' scenario in comparison with current legislation (CLE) 'baseline' emission scenario. Spatial analysis identifies a rapid increase in anthropogenic PM2.5 in the eastern Indian states of Jharkhand, Chhattisgarh and Odisha, Peninsular India, and Delhi National Capital Region. Our results identify the near future pollution hotspots that would be useful in air quality management planning for the near future. Highlights: Spatial distribution of anthropogenic PM2.5 is projected till 2040 over India. The statistical model is trained by RegCM meteorology and ECLIPSE emission. Significant difference in projected PM2.5 for 'baseline' and 'mitigation' emission scenarios. Projected meteorology partially negates the impact of rising emission under both RCP4.5 and 8.5 scenarios. Maximum impact is expected in Delhi NCR, Jharkhand, Chhattisgarh and Odisha.